Sie sind auf Seite 1von 15

CHAPTER 1

SUCCESSIVE DIFFERENTIATION AND LEIBNITZ’S THEOREM

1.1 Introduction

Successive Differentiation is the process of differentiating a given function successively times and the results of such differentiation are called successive derivatives. The higher order differential coefficients are of utmost importance in scientific and engineering applications. Let be a differentiable function and let its successive derivatives be denoted by

function and let its successive derivatives be denoted by . Common notations of higher order Derivatives

.

Common notations of higher order Derivatives of

 

1

st Derivative:

or

oror

or or
 

or

or

2

nd Derivative:

or

oror

or

or

 

Derivative:

or

or

or

  Derivative: or or or or

or

1.2

Calculation of n th Derivatives

 

i. Derivative of

 
 

Let y

=

ii. Derivative of Let y =

,

is a

 
 

iii. Derivative of Let ⋮ iv. Derivative of Let ⋮ Similarly if v. Derivative of

iii. Derivative of

Let

iii. Derivative of Let ⋮ iv. Derivative of Let ⋮ Similarly if v. Derivative of Let
iii. Derivative of Let ⋮ iv. Derivative of Let ⋮ Similarly if v. Derivative of Let

iv. Derivative of

Let

Similarly if

v. Derivative of

Let

Similarly

where

Similarly if

and

Putting

of Let ⋮ iv. Derivative of Let ⋮ Similarly if v. Derivative of Let Similarly ⋮
of Let ⋮ iv. Derivative of Let ⋮ Similarly if v. Derivative of Let Similarly ⋮
of Let ⋮ iv. Derivative of Let ⋮ Similarly if v. Derivative of Let Similarly ⋮

Summary of Results

Function Derivative y = = y = = = = y = y = Example
Function
Derivative
y
=
=
y
=
=
=
=
y
=
y
=
Example 1 Find the
derivative of
Solution: Let

Resolving into partial fractions

= = ∴ = = !
=
=
=
=
!

Example 2

Find the

derivative of

 

Solution:

Let

 

=

(sin10

+ cos2

)

 

=

Example 3

Find Let y =

derivative of

 

Solution:

 

Example 4

Solution:

Example 5

Solution:

=

=

=

=

=

Find the

Let

Find the

Let

Now

derivative of

=

derivative of

–
Let Find the Let Now derivative of = derivative of – ∴ ⇒ – Example 6
Let Find the Let Now derivative of = derivative of – ∴ ⇒ – Example 6
Let Find the Let Now derivative of = derivative of – ∴ ⇒ – Example 6

Example 6

If

, prove that

Solution:

=

Let Find the Let Now derivative of = derivative of – ∴ ⇒ – Example 6

=

=

=

=

=

Example 7

Solution:

Find the

Let

derivative of

and

=

=

=

=

=

Differentiating above

times w.r.t. x, we get

Substituting

above times w.r.t. x , we get Substituting ⇒ such that Using De Moivre’s theorem ,

such that

Using De Moivre’s theorem, we get

where Example 8 Find the derivative of Solution: Let = where = and =
where
Example 8 Find the
derivative of
Solution: Let
=
where
=
and
=

Resolving into partial fractions

Differentiating

times w.r.t. , we get

Differentiating times w.r.t. , we get Substituting such that Using De Moivre’s theorem , we get
Differentiating times w.r.t. , we get Substituting such that Using De Moivre’s theorem , we get

Substituting

Differentiating times w.r.t. , we get Substituting such that Using De Moivre’s theorem , we get
Differentiating times w.r.t. , we get Substituting such that Using De Moivre’s theorem , we get
Differentiating times w.r.t. , we get Substituting such that Using De Moivre’s theorem , we get

such that

Using De Moivre’s theorem, we get

Substituting such that Using De Moivre’s theorem , we get where Example 9 If Solution: ⇒
Substituting such that Using De Moivre’s theorem , we get where Example 9 If Solution: ⇒
Substituting such that Using De Moivre’s theorem , we get where Example 9 If Solution: ⇒

where

Example 9 If Solution:

⇒ ∴ Example 10 If Solution: ⇒ =
Example 10
If
Solution:
=

,

show that

=

,

show that

(

⇒ ( ) = 1 Differentiating both sides w.r.t. , we get ( ) + =

)

= 1

Differentiating both sides w.r.t.

, we get

(

⇒ ( ) = 1 Differentiating both sides w.r.t. , we get ( ) + =

)

+

⇒ ( ) = 1 Differentiating both sides w.r.t. , we get ( ) + =

= 0

1. derivative of

Find the

2. derivative of Ans.

Find the

Exercise 1 A Ans.
Exercise 1 A
Ans.

If

3. ,

4.

5.

If

If

6.

If

,

show that

, find

, show that

i.e. the

derivative of

Ans. , find Ans.
Ans.
, find
Ans.

i.e. the

where

derivative of

7. Find

8.

9.

If y =

If

differential coefficient of =

Ans.

, show that

=

, show that

=

1.2 LEIBNITZ'S THEOREM If and are functions of such that their derivatives exist, then the derivative of their product is given by

where

and

represent

derivatives of

and

respectively.

Example11

Find the

derivative of

Solution:

Let

and

Then

Then and

and

By Leibnitz’s theorem, we have

and Then and By Leibnitz’s theorem, we have ⇒ Example 12 Find the derivative of Solution:
and Then and By Leibnitz’s theorem, we have ⇒ Example 12 Find the derivative of Solution:

Example 12

Find the

derivative of

Solution: Let

and

Then

we have ⇒ Example 12 Find the derivative of Solution: Let and Then By Leibnitz’s theorem,

By Leibnitz’s theorem, we have

we have ⇒ Example 12 Find the derivative of Solution: Let and Then By Leibnitz’s theorem,
Example 13 If , show that = 0 Solution: Here ⇒ ⇒ Differentiating both sides
Example 13 If , show that = 0 Solution: Here ⇒ ⇒ Differentiating both sides

Example 13

If

, show that = 0

Solution:

Here

Differentiating both sides w.r.t.

=

, we get

 

Using L

z’ s theorem, we get

Example 14

If

Prove that

Solution:

)

Differentiating both sides w.r.t.

, we get

Using Leibnitz’s theorem

Example 15 If

Solution:

Here

, show that

. Also find

……

=

……

Usi

Putting

(1- Differentiating w.r.t.

, we get

L

z’

h

r

, we get

in ,and and

……

Putting

in

Putting

in the above equation, we get

=

= 0

=

Example 16 If

Example 16 If show that

show that

Solution:

Here

……

= Differentiating above equation w.r.t.

Differentiating above equation

times w.r.t.

, we get

……

u

L

. Also find

z’

h

r

w

.

……

To find

Putting

in , and

Also putting

and in ,we get

Putting

in the above equation, we get

=

Example 17 If

, show that

. Also find

Solution:

Here

 

  ⇒ …… ②

……

Differentiating equation

……

times w.r.t.

u

L

z’

theorem

To find

Also putting

……in , and , we get

Putting and in ,we get

Putting

in the above equation, we get

=

=

=

0

Example18

Solution:

If

Here

= = = 0 ⇒ Example18 Solution: ⇒ ⋮ If Here and show that … ①

and

show that

……

Squaring both the sides, we get

Differentiating the above equation w.r.t.

Differentiating the above equation

……

times w.r.t.

Also find

, we get

u

L

z’

To find

Putting

and

……

in , and , we get

h

r

w

Also putting

Putting

=

in ,we get

in the above equation, we get

=

= 0

1 .Find

Ans.

2. Find

, if

, if

3. If

4. If

Exercise 1 B

, prove that

Ans.

), prove that

5. If

6 If

7. If

Ans.

1 B , prove that Ans. ), prove that 5. If 6 If 7. If Ans.

, prove that

show that

and

, show that

. Also find

.

8.

If

prove that